THE EFFECT OF EMPLOYEE EMPOWERMENT AND WORKPLACE ENVIRONMENT ON EMPLOYEE JOB SATISFACTION AND LOYALTY AS A MEDIATION VARIABLE IN UMKM IN MADURA - Safvitri, Cindy; Buyung Aulia Safrizal, Helm; Zaki Kurniawan, Moh. (JURNAL EKBIS, 2024)
This study aims to analyze the effect of employee empowerment and work environment on job satisfaction, and to test employee loyalty as a mediating variable in the relationship in MSMEs in Madura. This study uses a quantitative approach using a questionnaire to measure the number of responses or respondents using primary data. The results of the study indicate that employee empowerment and work environment have a positive and significant effect on employee job satisfaction. Employees who are satisfied with empowerment and the work environment tend to have higher loyalty to the organization. This study provides an important contribution for MSME managers in Madura in understanding the importance of empowerment and a conducive work environment to increase employee satisfaction and loyalty